PEMANFAATAN LIMBAH LATEKS KARET ALAM DENGAN PENGISI BUBUK PELEPAH PISANG SEBAGAI ADSORBEN MINYAK - Ismail Fahmi Hasibuan, Edward Tandy, Hamidah Harahap (Universitas Sumatera Utara, 2012)
The use of waste of natural rubber latex with banana sheats powder filler to serve as a more useful product that is used as adsorbent of oil. The process begins with drying the adsorbent manufacture banana and polished up to 100 mesh size. Then the banana powder mixed with waste latex with variations of 10 and 20% (w / w). The analysis of the ability of the adsorbent adsorption isotherms using the Langmuir equation and Freundlich isotherm equation. Research carried out by the batch process and the use of lubricating oil as the adsorbate. The results obtained showed the addition of banana powder as filler waste adsorbent adsorption of latex increases the ability of the oil adsorbent. The conclusion of the analysis showed an increase in the number of characteristics adsroben banana powder can enhance the adsorption of adsorbent.Keywords : natural rubber latex waste, banana sheaths powder, adsorbent oil, adsorption ability